A misaligned through magnesium sulfide connection plywood and a preparation method thereof
Patent Information
- Application Number
- CN202611332567.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-31
- Publication Date
- 2026-10-16
AI Technical Summary
[0006]本发明的目的是提供一种错位贯通硫氧镁连接胶合板及其制备方法,以解决现有的胶合板较难兼顾轻量化与高承载抗分层性能的技术问题
[0029] 1. The filling slurry without cenospheres is concentrated in the spacer hole group, and a lightweight continuous adhesive layer containing closed-shell cenospheres is used in the area outside the hole. The surface density is significantly reduced, and the discrete dense connector provides a reliable load transfer path locally, resulting in a high wet adhesive strength retention rate.
Smart Images

Figure CN122914306A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of plywood technology, and in particular to a misaligned through-hole magnesium oxysulfide bonded plywood and its preparation method. Background Technology
[0002] Plywood is typically made by assembling multiple layers of wood veneer with the fiber direction of adjacent layers crossed, and then pressing them together using organic resin adhesives or inorganic gelling adhesives. In addition to requiring certain bonding strength and flexural stiffness, plywood used in construction also needs to meet requirements for surface density, water resistance, dimensional stability, flame retardancy, and volatile organic compound (VOC) emissions.
[0003] Magnesium oxysulfate cementitious systems, with lightly calcined magnesium oxide, magnesium sulfate, and water as the main reactants, can form an inorganic cementitious phase. Using this system for plywood bonding is beneficial for obtaining a bonded interface with low organic content and certain heat resistance. However, if a dense magnesium oxysulfate slurry with a high sizing application rate is used at all bonded interfaces, the surface density of the plywood and the amount of inorganic phase will increase; simply reducing the sizing application rate or directly introducing large amounts of lightweight particles may result in insufficient sizing, interconnected pores, decreased wet bonding, or insufficient local stress transfer. To resolve these contradictions, a common approach is to create a network of pores within the plywood and fill them with cementitious material to form a bond, providing localized reinforcement.
[0004] Furthermore, when the two outer core boards are provided with large holes and the middle core board is provided with small holes to form a necked structure of large holes, small holes, and large holes, if the three holes are completely coaxial, the axis of the necked structure remains straight, and the bearing shoulders at the two internal adhesive interfaces are axially symmetrically distributed. When subjected to interface deformation caused by in-plane shear or water-wet cycle, the load transmission path of this structure is straight, and cracks can extend directly along the adhesive interface. The resistance to push-out and the resistance to interface delamination of the connector are still insufficient. If the middle small hole is simply offset too much relative to the outer large hole, the projection of the upper and lower through holes is discontinuous, the filling slurry cannot form a cross-layer whole, and the reinforcing effect of the connector will fail.
[0005] Therefore, how to reduce the weight of the sheet metal by utilizing the necking structure while simultaneously improving the connector's resistance to shearing and interface peeling through optimized hole arrangement is a problem that needs to be solved. Summary of the Invention
[0006] The purpose of this invention is to provide a staggered, through-hole magnesium oxysulfate bonded plywood and its preparation method, so as to solve the technical problem that existing plywood is difficult to balance lightweight and high load-bearing and anti-delamination performance.
[0007] The above-mentioned technical objective of this invention is achieved through the following technical solution: a staggered, through-hole magnesium oxysulfate bonded plywood, composed of 2n+1 layers of wood veneer, where n is 3, 4, or 5. When numbered sequentially from one surface to the other, the nth, n+1th, and n+2th layers of wood veneer constitute a perforated core layer group located in the middle of the board thickness, while the remaining wood veneers outside the perforated core layer group remain intact. The two outer veneers of the perforated core layer group are provided with coaxial circular first through holes, and the middle veneer is provided with a smaller diameter circular second through hole offset relative to the first through hole.
[0008] The overlapping area of the orthographic projection of the second through hole in the direction perpendicular to the board surface and the orthographic projection of the first through hole accounts for 60% to 90% of the orthographic projection area of the second through hole. A continuous and dense magnesium oxysulfate solidified body is formed in the two corresponding first through holes and one second through hole, which penetrates the three perforated internal veneers and the two adhesive interfaces therein, forming a through-connector that is wider at both ends and offset and necked in the middle.
[0009] A closed-shell cenosphere magnesium oxysulfate adhesive layer is installed in the bonding area outside the through holes between adjacent veneers. The magnesium oxysulfate through-connector is formed by curing the filling slurry without closed-shell cenospheres during preparation; the closed-shell cenosphere magnesium oxysulfate adhesive layer is formed by curing the adhesive slurry with closed-shell cenospheres. The inorganic cementitious matrix of both uses a magnesium oxide-magnesium sulfate-water system and is cured and bonded together in the contact area.
[0010] Preferably, when n=3, the plywood has a seven-layer structure, with the third to fifth layers being perforated core layers; when n=4, the plywood has a nine-layer structure, with the fourth to sixth layers being perforated core layers; and when n=5, the plywood has an eleven-layer structure, with the fifth to seventh layers being perforated core layers. The fiber directions of adjacent veneers are arranged in a cross pattern, and the perforated core layers are located in the middle of the board thickness, with the outer intact veneers maintaining the continuity of the board surface.
[0011] Preferably, both the first and second through holes are circular holes. The diameter Do of the first through hole is 10–14 mm, the diameter Dm of the second through hole is 7–10 mm, the Dm / Do ratio is 0.65–0.85, the hole center offset e is 3–5 mm, and the hole spacing p is 55–70 mm. Do, Dm, and e are selected in a coordinated manner, ensuring that the projected overlap rate calculated by dimensions is 60%–90%. During batch processing, the allowable deviations of Do, Dm, and e are ±0.2 mm, ±0.2 mm, and ±0.2 mm, respectively, and the allowable deviation of p is ±0.5 mm. The center deviation of the two outer core plates corresponding to the first through hole is no greater than 0.3 mm.
[0012] Preferably, the second through hole in an adjacent hole row is offset alternately in the +x and -x directions relative to the corresponding first through hole; the width of the non-perforated frame around the perforated core layer group is calculated based on the shortest distance from the edge of the plate surface to the edge of the nearest through hole, and is not less than 30mm.
[0013] Preferably, the closed-shell cenospheres have a D90 of no more than 100 μm, a water absorption rate of no more than 5% per hour, an apparent particle density of 0.35–0.75 g / cm³, and a volume fraction of 25%–35% based on the wet apparent volume of the adhesive slurry. After low-speed stirring and pressing at a pressure not exceeding 1.3 MPa, the retention rate of intact closed-shell particles is no less than 90%.
[0014] Preferably, based on the active magnesium oxide in the light-burned magnesium oxide powder, the molar ratio of active magnesium oxide to magnesium sulfate is 7.7–8.3:1, and the molar ratio of total water to magnesium sulfate is 19–21:1. The total water includes added water and water of crystallization. The base slurry also includes 0.4%–0.6% citric acid and 0.15%–0.25% hydroxypropyl methylcellulose by mass of the light-burned magnesium oxide powder.
[0015] The present invention also provides a method for preparing the plywood, including veneer moisture conditioning and selection, simultaneous punching of three adjacent internal veneers, preparation of magnesium oxysulfate base slurry, diversion of the same batch of base slurry, application of adhesive layer by layer from bottom to top and staged filling of holes on the release liner, alignment and assembly, pre-pressing, warm and pressurized pressing and constraint curing.
[0016] Preferably, the fresh density of the filling grout is 1.45–1.65 g / cm³, and the fresh density of the adhesive grout is 1.15–1.30 g / cm³, which is 78%–82% of the fresh density of the filling grout; the wet application amount of the adhesive grout at each adhesive interface is 150–180 g / (m²·adhesive layer).
[0017] Preferably, a cylinder with an inner diameter of 30 mm and a height of 30 mm is used to measure the mini slump expansion of the filling slurry, which is controlled to be 45–60 mm; the water bleeding rate of the filling slurry after standing for 30 min is not greater than 1.0%. Filling slurry is added quantitatively to a single hole group at ±5% of the theoretical wet filler mass, and after filling, the slurry is flush with or 0–0.20 mm above the hole opening.
[0018] The initial setting time of the grout and the adhesive grout were measured separately, and the shorter one was used as the control initial setting time. The moment when the lightly calcined magnesium oxide powder began to contact the magnesium sulfate solution was taken as t0. The time from t0 to the temperature and pressure pressing equipment displaying 0.25 MPa should not exceed 30 minutes and should not exceed 50% of the control initial setting time; the time from the end of pre-pressing to the temperature and pressure pressing equipment displaying 0.25 MPa should not exceed 5 minutes.
[0019] Preferably, the slab is first pre-pressed at 0.25-0.35 MPa for 2-3 min, and then pressed at 50-60℃ and 1.0-1.3 MPa for 45-60 min; after pressing, the pressure is released in stages, and after the slab is removed, it is flattened and constrained for 4-8 h, and then cured in an environment of 23±2℃ and 60%±10% relative humidity.
[0020] In this specification, the projection overlap rate R is determined by the following formula: Project the outline of the second through hole onto the plane where the first through hole is located along the direction perpendicular to the plate surface, and obtain the overlapping area Aoverlap and the projected area Ahole of the second through hole using image analysis or computer-aided design methods, and R = Aoverlap / Ahole × 100%. For two first through holes arranged coaxially, the projected outline of either first through hole is used as the calculation boundary.
[0021] In this specification, the active magnesium oxide content is determined according to YB / T 4019—2020, and the amount of lightly calcined magnesium oxide powder to be fed is calculated accordingly. The moisture content of the single plate is determined by the drying method: the sample is dried at 103±2℃ until the mass change between two consecutive weighings is no more than 0.1% of the initial mass, and calculated as (mass before drying − oven-dry mass) / oven-dry mass × 100%.
[0022] In this instruction manual, D90 refers to the particle size of 90% of the particles not exceeding this value based on the cumulative volume distribution; the 1-hour water absorption rate is calculated as the mass m0 of the dried particles and the mass m1 of the particles after soaking in water at 23±2℃ for 1 hour, filtering, and removing surface free water, i.e., (m1−m0) / m0×100%. The density of the freshly mixed material was determined at 23±2℃ using a calibrated 100 mL constant-volume container: the slurry was not vibrated or pressurized and the container was filled to the brim. The container was then gently tapped 10 times along its outer wall, leveled, and weighed. Three parallel measurements were taken for each branch, and the average value was recorded.
[0023] In this instruction manual, the initial setting time of both the filling grout and the bonding grout is determined using the same Vicat needle device starting from t0: the grout is loaded into a circular mold with an inner diameter of 65 mm and a height of 40 mm, and a needle with a diameter of 1.13±0.05 mm and a total moving mass of 300±1 g is used. Measurements are taken every 2 minutes before the expected initial setting time. Initial setting is considered achieved when the needle is 4±1 mm from the bottom plate. The shorter initial setting time of the two branches is used to control the construction window. The moment when the slab is subjected to a pressure of 0.25 MPa is the moment when the average pressure displayed by the thermo-pressurization equipment first reaches 0.25 MPa.
[0024] In this instruction manual, the method for determining the mini slump spread is as follows: A cylinder with an inner diameter of 30±0.2 mm and a height of 30±0.2 mm is placed on a flat plate, filled with slurry in one go, and leveled. The cylinder is then lifted vertically within 2±1 s. Ten s after lifting the cylinder, two mutually perpendicular spread diameters are measured and their average value is taken. The bleeding rate is determined using a 100 mL stoppered graduated cylinder. After standing at 23±2℃ for 30 min, the volume of free liquid at the top, Vb, is read and calculated as Vb / 100×100%.
[0025] The theoretical wet filler mass m0 of a single borehole group is calculated as m0 = ρf·π[Do²(tu+tl)+Dm²tm] / 4000, where ρf is the fresh density of the filler slurry in g / cm³; Do and Dm are the diameters of the first and second through holes, respectively; tu, tm, and tl are the thicknesses of the perforated core plates on the upper, middle, and lower sides, respectively, all in mm; and m0 is in g. The metering device is calibrated by discharging material 20 times consecutively before construction, and the actual added mass of a single borehole group deviates from m0 by no more than ±5%.
[0026] In this specification, the filling state of the through-connector is used as a process quality evaluation indicator rather than a necessary limitation of the claims in this application. Five hole groups are taken from the center and quarter points of each plate. Samples are taken and polished on a vertical cutting plane containing the axes of the first and second through holes, and image analysis is performed using pre-frozen lighting, magnification, and grayscale thresholds. The filling rate is the ratio of the actual dense phase area within the cross-section to the theoretical filling area enclosed by the hole walls and the two adhesive interfaces. The maximum cavity size is the largest Freette diameter of the cavity in all five cross-sections.
[0027] Compared to full-width dense inorganic bonding solutions, this invention concentrates the filler slurry without cenospheres in the spacer hole group and uses a continuous adhesive layer containing closed-shell cenospheres in the area outside the holes, which helps reduce the amount of inorganic phase used in non-critical areas. Large coaxial holes on the outer side form two heads, while offset small holes in the middle form a non-coaxial waist; 60%–90% projected overlap ensures continuous slurry contact, and the two internal interfaces form asymmetrical bearing shoulders and broken-line load paths with opposite directions. Adjacent hole rows are offset in opposite directions to balance directionality, and the splitting of the same batch of base slurry reduces the difference in slurry age and rheological state between the two branches.
[0028] The beneficial effects of this invention are:
[0029] 1. The filling slurry without cenospheres is concentrated in the spacer hole group, and a lightweight continuous adhesive layer containing closed-shell cenospheres is used in the area outside the hole. The surface density is significantly reduced, and the discrete dense connector provides a reliable load transfer path locally, resulting in a high wet adhesive strength retention rate.
[0030] 2. The large coaxial hole on the outer side and the offset small hole in the middle form a non-coaxial head and waist, forming an asymmetrical bearing shoulder with opposite directions at the two internal adhesive interfaces. The shear load transmission path changes from a straight line to a broken line. The resistance to push-out and the resistance to delamination are significantly better than the coaxial necking structure. At the same time, the reverse offset of adjacent hole rows eliminates the directional weakness that may be caused by unidirectional offset.
[0031] 3. The filling grout and the bonding grout are derived from the same batch of base grout, and have the same inorganic cementitious matrix composition, similar grout age and rheological state. They are cured together during the temperature and pressure bonding process to form a strong bond with continuous chemical composition. Attached Figure Description
[0032] To more clearly illustrate the technical solutions in the embodiments of the present invention, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0033] Figure 1 This is a schematic diagram of the structure of a misaligned through-hole magnesium oxysulfide bonded plywood and its preparation method provided in an embodiment of the present invention;
[0034] Figure 2 This is a schematic diagram showing the disassembled structure of three adjacent perforated core boards in an embodiment of the present invention;
[0035] Figure 3 This is a schematic diagram of the hole array and the alternating offset relationship between adjacent hole rows in an embodiment of the present invention;
[0036] Figure 4 This is a schematic flowchart of the plywood preparation method in an embodiment of the present invention;
[0037] Figure 5 This is a comparison diagram of density in an embodiment of the present invention;
[0038] Figure 6 This is a comparison diagram of wet bonding strength in embodiments of the present invention;
[0039] Figure 7 This is a comparison chart of the layering rate in an embodiment of the present invention.
[0040] In the diagram: 1. Intact wood veneer; 2. Perforated core board; 21. First through hole; 22. Second through hole; 3. Dense magnesium oxysulfate through connector; 31. Head; 32. Waist; 4. Continuous lightweight magnesium oxysulfate adhesive layer; 5. Perforated frame. Detailed Implementation
[0041] The technical solution of the present invention will now be clearly and completely described with reference to specific embodiments. Obviously, the described embodiments are merely some, not all, of the embodiments of the present invention. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.
[0042] This invention specifically provides a misaligned, through-type magnesium oxysulfide bonded plywood and its preparation method, please refer to the accompanying drawings. Figure 1-7 The present invention will be further illustrated by the examples and comparative examples.
[0043] Unless otherwise stated, the percentage of additives is based on the mass of lightly calcined magnesium oxide powder, and the volume fraction of closed-shell cenospheres is based on the wet apparent volume of the adhesive mortar.
[0044] The plywood of the present invention is composed of 2n+1 layers of complete wood veneer, where n is 3, 4 or 5, and the fiber directions of adjacent layers are crossed.
[0045] When numbering sequentially from one side of the surface to the other, the nth layer, the n+1th layer, and the n+2th layer constitute a perforated core layer group, while the remaining outer single plates remain intact. The two outer single plates of the perforated core layer group are provided with coaxial circular first through holes, and the middle single plate is provided with a smaller diameter circular second through hole that is offset relative to the first through hole.
[0046] In practice, the area where the orthographic projection of the second through hole in the direction perpendicular to the plate surface overlaps with the orthographic projection of the first through hole accounts for 60% to 90% of the orthographic projection area of the second through hole.
[0047] Specifically, both the first and second through holes are circular holes. The diameter Do of the first through hole is 10-14 mm, the diameter Dm of the second through hole is 7-10 mm, the Dm / Do ratio is 0.65-0.85, the hole center offset e is 3-5 mm, and the hole spacing p is 55-70 mm. Do, Dm, and e are selected in a coordinated manner to ensure that the projection overlap rate calculated by size is 60%-90%. The second through holes in adjacent hole rows are alternately offset in opposite directions relative to the corresponding first through holes. The width of the non-perforated frame around the perforated core layer group is not less than 30 mm.
[0048] During implementation, the closed-shell cenospheres should have a D90 of no more than 100 μm, a water absorption rate of no more than 5% in 1 hour, and an apparent particle density of 0.35–0.75 g / cm³. After low-speed stirring and pressing at a pressure no higher than 1.3 MPa, the retention rate of the number of intact closed-shell particles should be no less than 90%.
[0049] The molar ratio of active magnesium oxide to magnesium sulfate in the light-burned magnesium oxide powder is 7.7–8.3:1, and the molar ratio of total water to magnesium sulfate is 19–21:1. The basic slurry also includes 0.4%–0.6% citric acid and 0.15%–0.25% hydroxypropyl methylcellulose by mass of the light-burned magnesium oxide powder.
[0050] When n=3, the plywood has a seven-layer structure, with the third to fifth layers being a perforated core layer group;
[0051] When n=4, it is a nine-layer structure, with the fourth to sixth layers being perforated core layers;
[0052] When n=5, it is an eleven-layer structure, with the fifth to seventh layers being perforated core layers.
[0053] In this design, the fiber directions of adjacent veneers are arranged in a cross pattern, and the perforated core layer is located in the middle of the veneer thickness.
[0054] Furthermore, rotary-cut poplar veneer was used during implementation, with the moisture content of the veneer adjusted to 9%–11%. Veneers with through cracks, decay, or large knots at the proposed hole locations were discarded. The first through holes were arranged in a square array, and the second through holes in adjacent rows were alternately offset along the +x and -x directions.
[0055] Based on 1.000 kg of lightly calcined magnesium oxide powder, magnesium sulfate heptahydrate, added water, citric acid and hydroxypropyl methylcellulose were weighed according to Table 1. The total water in the table includes added water and the water of crystallization introduced by magnesium sulfate heptahydrate.
[0056]
[0057] During implementation, magnesium sulfate heptahydrate is first dissolved in external water and citric acid is added. The solution temperature is adjusted to 20-25℃. Hydroxypropyl methylcellulose and lightly calcined magnesium oxide powder are premixed and slowly added to the solution while stirring. The moment when magnesium oxide powder first comes into contact with the solution is recorded as t0.
[0058] Specifically, the base slurry from the same batch is split before initial setting: no cenospheres are added to the filling branch, and cenospheres are added to the bonding branch and stirred at low speed for 60-90 seconds.
[0059] The fresh density, mini slump spread, and 30-minute bleeding rate were measured within 2 minutes after the slurry was split.
[0060] The mini slump spread of the filling grout should be controlled at 45-60 mm, and the water bleeding rate should not exceed 1.0%. The adhesive grout should be able to be continuously rolled or scraped without obvious segregation.
[0061] The fresh density of the grout is 1.45–1.65 g / cm³, the fresh density of the adhesive slurry is 1.15–1.30 g / cm³ and is 78%–82% of the fresh density of the grout, and the wet application amount of the adhesive slurry at each bonding interface is 150–180 g / (m²·adhesive layer).
[0062] It is worth noting that the theoretical wet packing mass m0 of a single hole group is calculated as m0=ρf·π[Do²(tu+tl)+Dm²tm] / 4000.
[0063] Wherein, ρf is the fresh density of the grout, and the units of Do, Dm, tu, tm and tl are mm, respectively. The actual added mass deviates from m0 by no more than ±5%. After filling the hole, the grout is flush with or 0 to 0.20 mm above the hole opening.
[0064] Furthermore, the preparation process of the staggered through-hole magnesium oxysulfate bonded plywood includes placing a rigid release bearing plate on the assembly platform, and laying the plywood layer by layer from bottom to top according to the predetermined layer number without flipping it.
[0065] In the non-porous interface, adhesive slurry is continuously applied to one side of the upper surface of the lower veneer, and the internal interface of the perforated core layer adopts a removable mask with a plugging boss to keep the through-hole area away from the adhesive slurry.
[0066] In this process, after laying the lower first through-hole core board, the through-hole is first covered on its upper surface and adhesive grout is continuously applied to the outside of the hole, and then the first through-hole is quantitatively filled; then the middle second through-hole core board is laid in alignment, so that the second through-hole and the lower first through-hole maintain a specified projection overlap relationship, and the newly added filling grout is brought into contact with the filling grout below that has not yet set and fills the second through-hole from the second through-hole downwards, and then the second through-hole is covered and adhesive grout is continuously applied to the outside of the hole, and the upper first through-hole core board is laid in alignment, and the filling is carried out from the bottom of its first through-hole upwards.
[0067] During implementation, when filling the first through hole on the upper side, an exhaust channel should be reserved on the side away from the discharge nozzle. After each filling, the slurry surface should be flush with or higher than the orifice by 0 to 0.20 mm.
[0068] After the first through hole on the upper side is filled, lay down the upper complete veneer with adhesive grout applied to the lower surface, so that the hole filling grout contacts the complete veneer; then continue to complete the cross assembly of the remaining complete veneers.
[0069] The time from the completion of filling the first through hole on the top side to the complete coverage of the single board shall not exceed 2 minutes, and the time from the completion of filling the three-layer hole group to the completion of the whole board assembly shall not exceed 5 minutes.
[0070] The initial setting time of the grout and the adhesive grout were measured separately, and the shorter of the two was used as the control initial setting time.
[0071] Specifically, the time from t0 to the temperature and pressure pressing equipment displaying the slab being subjected to 0.25MPa pressure shall not exceed 30 minutes and shall not exceed 50% of the controlled initial setting time; the time from the end of pre-pressing to the temperature and pressure pressing equipment displaying 0.25MPa pressure shall not exceed 5 minutes.
[0072] The slab is first pre-pressed at 0.25-0.35 MPa for 2-3 minutes, and then warm-pressed at 50-60℃ and 1.0-1.3 MPa for 45-60 minutes.
[0073] After pressing, the pressure is successively reduced to 0.6MPa and held for 30s, then reduced to 0.2MPa and held for 30s before being released to zero. After the board is removed, it is flattened and constrained under a surface pressure of 2-5kPa for 4-8 hours, and then cured for 14 days in an environment of 23±2℃ and 60%±10% relative humidity.
[0074] Example 1
[0075] In this embodiment, a 12mm thick plywood is prepared using seven layers of poplar veneer. The fiber orientation of the veneer is 0° / 90° / 0° / 90° / 0° / 90° / 0°. The third to fifth layers form a perforated core layer group. The thickness of each veneer layer is 1.80mm, and the total thickness before gluing is 12.60mm. A 12.00mm thick limiting strip is used, and the compression rate is 4.8%.
[0076] Specifically, the third and fifth layers are machined with a first through hole of Do=12mm, the fourth layer is machined with a second through hole of Dm=8mm and offset by e=4mm, the projection overlap rate R=74.17%, the hole spacing p=60mm, and the width of the hole-free border is 35mm.
[0077] Among them, using formula A (active MgO / MgSO4=8.0∶1, total H2O / MgSO4=20∶1), after the same batch of base slurry was split: the fresh density of the pore-filling slurry was 1.55 g / cm³, the water bleeding rate after standing for 30 min was 0.5%, and the mini slump spread was 52 mm; 30 vol% closed-shell cenospheres were added to the adhesive branch, the fresh density was 1.24 g / cm³, the wet application rate was 160 g / (m²·adhesive layer), and the cenosphere closed-shell retention rate was 94%.
[0078] During implementation, pre-compression was carried out at 0.30MPa for 2.5 minutes; temperature compression was carried out at 55℃ and 1.2MPa for 55 minutes. After staged decompression, the plates were constrained under a surface pressure of 2-5kPa for 6 hours and then cured in a standard environment for 14 days.
[0079] Example 2
[0080] The difference between this embodiment and Embodiment 1 is as follows: the offset of the second through-hole in the fourth layer is e=3.2mm, and the projected overlap rate is R=86.47%; the batching scheme B is adopted (active MgO / MgSO4=7.7∶1, total H2O / MgSO4=19∶1); the fresh density of the filling slurry is 1.50g / cm³, the adhesive slurry is 1.22g / cm³, and the ratio is 81.3%; the volume fraction of cenospheres is 25%; the application rate of adhesive is 150g / (m²·adhesive layer); the pre-compression is 0.25MPa / 2min, the temperature compression is 50℃ / 1.0MPa / 45min, and the constraint is 4h. The rest is the same as in Embodiment 1.
[0081] Example 3
[0082] The difference between this embodiment and Embodiment 1 is as follows: Do=10mm for the third and fifth layers, Dm=7mm for the fourth layer, e=3.8mm, R=63.73%; hole spacing 70mm, no-hole border 40mm; using batching scheme C (active MgO / MgSO4=8.3∶1, total H2O / MgSO4=21∶1); fresh density of the pore-filling slurry 1.60g / cm³, adhesive slurry 1.28g / cm³; cenosphere volume fraction 35%; adhesive application rate 180g / (m²·adhesive layer); pre-compression 0.35MPa / 3min, temperature compression 60℃ / 1.3MPa / 60min, constraint 8h, the rest is the same as in Embodiment 1.
[0083] Example 4
[0084] The difference between this embodiment and Embodiment 1 is as follows: Do=14mm, Dm=10mm, e=5mm, R=67.16%; the fresh density of the filling slurry is 1.58g / cm³, and the density of the adhesive slurry is 1.25g / cm³; the amount of adhesive applied is 170g / (m²·adhesive layer). Everything else is the same as in Embodiment 1.
[0085] Example 5
[0086] The difference between this embodiment and Embodiment 1 is that Do=10mm, Dm=8.5mm, e=3mm, Dm / Do=0.850, and R=69.56%. The rest is the same as in Embodiment 1.
[0087] Example 6
[0088] This embodiment uses nine layers of poplar veneer to prepare a 15mm thick plywood, with the fourth to sixth layers being a perforated core layer assembly. The three core veneer layers are each 1.80mm thick, and the remaining six intact veneers are each 1.725mm thick, resulting in a total thickness of 15.75mm before adhesive application. A 15.00mm thick limiting strip is used, with a compression rate of 4.8%. The perforation parameters are the same as in Example 1. The slurry uses formulation A and 30 vol% cenospheres, with an adhesive application rate of 160g / (m²·layer). The plywood is heated at 55℃ and 1.2MPa for 60 minutes. The rest is the same as in Example 1.
[0089] Example 7
[0090] This embodiment uses eleven layers of poplar veneer to prepare 18mm thick plywood, with the fifth to seventh layers being perforated core layers. The three core veneer layers are each 1.80mm thick, and the remaining eight intact veneers are each 1.6875mm thick, resulting in a total thickness of 18.90mm before adhesive application. An 18.00mm thick limiting strip is used, with a compression rate of 4.8%. The perforation parameters are the same as in Example 4. The slurry uses formulation A and 30 vol% cenospheres, with an adhesive application rate of 170g / (m²·layer). The plywood is heated at 60℃ and 1.3MPa for 60 minutes. The rest is the same as in Example 4.
[0091] Comparative Example 1
[0092] This comparative example does not include perforated groups. A dense magnesium oxysulfate slurry without cenospheres was applied to all six bonding interfaces at a rate of 350 g / (m²·layer). The remaining veneer, slurry formulation, and pressing procedures were the same as in Example 1.
[0093] Comparative Example 2
[0094] This comparative example does not include perforated groups. A lightweight adhesive mortar containing 30 vol% cenospheres was applied to all six bonding interfaces at a rate of 160 g / (m²·layer). The rest was the same as in Example 1.
[0095] Comparative Example 3
[0096] This comparative example uses a hole array with Do=12mm and Dm=8mm, but e=0 (completely coaxial) and R=100%. The remaining hole array, slurry, sizing amount and pressing process are the same as in Example 1.
[0097] Comparative Example 4
[0098] In this comparative example, Do = 12mm, Dm = 8mm, e = 6.2mm, and R = 39.87%, which is lower than the 60% lower limit. The rest is the same as in Example 1.
[0099] Comparative Example 5
[0100] In this comparative example, Do=12mm, Dm=8mm, e=11mm, R=0, and the projections of the three holes are not connected. Everything else is the same as in Example 1.
[0101] Comparative Example 6
[0102] This comparative example uses the same hole group as in Example 1, but the lightweight branch does not have floating beads added. The adhesive application rate, calculated based on the equal wet film volume, is approximately 200 g / (m²·adhesive layer). The rest is the same as in Example 1.
[0103] Comparative Example 7
[0104] This comparative example well group is the same as in Example 1, except that citric acid is not added and 0.20% HPMC is retained. The rest is the same as in Example 1.
[0105] Comparative Example 8
[0106] The structure and target dosage of this comparative example are the same as in Example 1, but the grout and adhesive grout are prepared separately, and the second batch of grout is prepared 10 minutes later at t0. The rest is the same as in Example 1.
[0107] During implementation, each group independently prepares no less than 5 boards. After curing, 50mm is cut off from each of the four sides. Then, samples are prepared according to the same sampling diagram that has been frozen in advance. The surface density, density, bonding strength, static bending strength, elastic modulus, 24h water absorption rate, and 24h thickness expansion rate are measured according to the applicable items of GB / T 9846-2015 and GB / T 17657-2022.
[0108] Longitudinal and transverse bending specimens were statistically analyzed separately, without merging the two directions.
[0109] For wet bonding, a uniform pretreatment was adopted: the specimens were soaked in water at 23±2℃ for 24 hours, and after being taken out, the surface free water was wiped off, and loading was started within 10 minutes.
[0110] Regarding the determination of delamination rate, one cycle consists of soaking in water at 23±2℃ for 24 hours, freezing at −20±2℃ for 24 hours, and restoring at 23±2℃ for 24 hours. After three cycles, the opening length of the adhesive layer on all board edges is measured, and the result is calculated as a percentage of the total opening length to the perimeter of the adhesive layer.
[0111] Regarding the hole group ejection test, a 16mm inner diameter support ring and a 7.5mm diameter flat-head indenter were used as the center, with a load applied at 1mm / min along the axis of the first through hole. The peak value before the through-connector lost its continuous load-bearing capacity was recorded. The apparent interlayer shear in the hole area was measured using short-span specimens containing a single hole group, with each group having the same direction and span-to-thickness ratio. The effective filling rate of the through-connector was only calculated based on the area occupied by the first magnesium oxysulfate curing body within the theoretically continuous area of the three core plates and two internal interfaces.
[0112] The test results are shown in Tables 2 to 5. The values in Tables 2, 3, and 5 are all taken as mean ± standard deviation. Figure 4 In the figure, " / " indicates that the group does not have a pore group (Comparative Examples 1 and 2) or has formed a through-connected body, so the pore filling rate index is not applicable. Comparative Example 5 does not form a through-connected body (effective filling rate is 0), but each pore contains an independent solidified phase, so the pore filling rate is listed separately. Figure 5 In the text, " / " indicates that the group does not form a continuous connection and does not have a measurable peak value for the hole group.
[0113] Table 2: Density, Areal Density and Bonding Indicators
[0114]
[0115] Table 3: Bending and Water Absorption Indicators
[0116]
[0117] Table 4: Durability, Appearance and Hole Filling Indicators
[0118]
[0119] Table 5: Local load-bearing capacity and interface durability in the borehole area
[0120]
[0121] It can be seen that, compared with the full-width unadulterated magnesium sulfate reference example 1, the areal density of Example 1 can be reduced by about 10.3%, and the retention rates of wet bonding strength, longitudinal static bending strength and longitudinal elastic modulus are about 95.5%, 97.6% and 97.3%, respectively, which reflects the performance retention under weight reduction conditions.
[0122] Compared to Comparative Example 2, which uses a lightweight adhesive layer without a through-hole connector, Example 1 showed an increase in surface density of approximately 1.5%, but an increase in wet bonding strength of approximately 44.8%, a 31 percentage point increase in wood breakage rate, and a 21 percentage point decrease in delamination rate. This indicates that the discrete dense connector effectively compensates for the shortcomings of a simple lightweight adhesive layer in terms of local bonding and load transfer.
[0123] Example 1 has a similar areal density to Comparative Example 3 with the coaxial hole group, but its wet bond strength, longitudinal static bending strength, and longitudinal elastic modulus are increased by approximately 7.7%, 7.1%, and 5.2%, respectively. Furthermore, the hole group of Example 1 has a peak ejection strength that is approximately 16.2% higher than that of Comparative Example 3 (430N vs 370N), an apparent interlaminar shear strength in the hole region that is approximately 16.4% higher (1.28MPa vs 1.10MPa), and a delamination rate at the two interfaces in the middle that is 5 percentage points lower.
[0124] This indicates that the offset of the intermediate through hole is not merely a simple geometric change, but rather generates a synergistic improvement in load-bearing capacity and anti-delamination by forming an asymmetric bearing shoulder and a non-collinear shear path. The C4 overlap rate is below the lower limit, the C5 projection is not connected and the through-fill rate is 0, which further verifies the criticality of the 60% to 90% overlap rate range as a boundary control.
[0125] Compared to Comparative Example 6 (with equal wet film volume comparison aperture) without cenospheres, Example 1 showed a reduction in areal density of approximately 3.0%, while retaining approximately 97.7%, 99.1%, and 98.8% of wet bonding strength, longitudinal static bending strength, and longitudinal elastic modulus, respectively, demonstrating a balance between the lightweighting of cenospheres and the preservation of the main body's performance.
[0126] Example 1 has a similar surface density to Comparative Example 8, which was prepared separately, but its dry and wet bond strengths are approximately 7.3% and 10.5% higher, respectively; the peak value of the pore group is approximately 10.3% higher; the apparent interlaminar shear strength in the pore area is approximately 14.3% higher; and the delamination rate at the two interfaces in the middle is 6.5 percentage points lower. This comparison demonstrates that splitting the base slurry from the same batch can effectively reduce the differences in slurry age and rheological state between the two branches, avoiding the interface weakening caused by separate slurry preparation.
[0127] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A staggered through-hole magnesium sulfate bonded plywood, comprising 2n+1 layers of wood veneer stacked sequentially along the thickness direction and an adhesive layer disposed between adjacent wood veneers, where n is 3, 4 or 5, the fiber directions of adjacent wood veneer layers are arranged to cross each other, and the wood veneers are numbered sequentially from one side surface of the plywood to the other side surface. Its features are: The nth, n+1th and n+2th layers of wood veneer constitute a continuous and adjacent perforated core layer group, and the wood veneers on the outside of the perforated core layer group are all unperforated and complete veneers. The nth and n+2th layers of wood veneer are each provided with a plurality of circular first through holes, and the first through holes are one-to-one and coaxially arranged. The (n+1)th layer of wood veneer is provided with a circular second through hole that corresponds one-to-one with the first through hole. The diameter of the second through hole is smaller than the diameter of the first through hole, and its central axis is offset relative to the central axis of the corresponding first through hole. The area where the orthographic projection of the second through hole in the direction perpendicular to the plate surface overlaps with the orthographic projection of the first through hole accounts for 60% to 90% of the orthographic projection area of the second through hole; The centers of the first through holes are arranged in a square array with a hole spacing of 55 to 70 mm. The second through holes in the same row are offset in the same direction, and the second through holes in adjacent rows are offset in opposite directions. Two corresponding first through holes and a second through hole located between them are provided with a continuous first magnesium oxysulfate curing body. The first magnesium oxysulfate curing body penetrates the perforated core layer and its two internal adhesive interfaces to form a through connection body with two heads, an offset waist and an asymmetric pressure-bearing shoulder. Multiple through connections are distributed at intervals along the plate surface. The first magnesium oxysulfate curing body is formed by curing a pore-filling slurry that has not added closed-shell cenospheres during preparation. A continuous second magnesium oxysulfate adhesive layer is provided between each adjacent wood veneer in the bonding area outside the first and second through holes. The second magnesium oxysulfate adhesive layer is formed by curing an adhesive paste containing closed-shell cenospheres. The volume fraction of the closed-shell cenospheres is 25% to 35% based on the wet apparent volume of the adhesive paste. The inorganic cementitious matrix of the first magnesium oxysulfate curing body and the second magnesium oxysulfate adhesive layer are both formed from raw materials including lightly calcined magnesium oxide powder, magnesium sulfate and water, and are cured and connected together at the contact points.
2. The staggered through-type magnesium oxysulfide bonded plywood according to claim 1, characterized in that: The plywood is composed of seven layers of wood veneer, with the third, fourth, and fifth layers of wood veneer forming the perforated core layer, and the first, second, sixth, and seventh layers of wood veneer being unperforated, complete veneers. The fiber directions of adjacent wood veneer layers are perpendicular to each other. The thickness of the plywood is 12 mm, and the thicknesses of the third, fourth, and fifth wood veneer layers are 1.6 to 2.0 mm, respectively.
3. The staggered through-type magnesium oxysulfide bonded plywood according to claim 2, characterized in that: The diameter Do of the first through hole is 10-14 mm, the diameter Dm of the second through hole is 7-10 mm, the Dm / Do ratio is 0.65-0.85, and the center distance e between the second through hole and the corresponding first through hole is 3-5 mm. The processing deviations of Do and Dm shall not exceed ±0.2 mm, the processing deviation of e shall not exceed ±0.2 mm, the processing deviation of hole spacing p shall not exceed ±0.5 mm, the measured center deviation of the corresponding first through hole on the nth and n+2th layers of wood veneer shall not exceed 0.3 mm, and the calculated projection overlap rate of Do, Dm and e shall be 60% to 90%.
4. The staggered through-type magnesium oxysulfide bonded plywood according to claim 3, characterized in that: The closed-shell cenospheres have a D90 of no more than 100 μm, a water absorption rate of no more than 5% in 1 h, and an apparent particle density of 0.35 to 0.75 g / cm³. After the cenospheres are mixed with adhesive slurry at low speed and pressed at a pressure of no more than 1.3 MPa, the proportion of intact closed-shell particles to the number of intact closed-shell particles before the addition is no less than 90%.
5. The staggered through-type magnesium oxysulfide bonded plywood according to claim 4, characterized in that: Based on the active magnesium oxide in the lightly calcined magnesium oxide powder, the molar ratio of active magnesium oxide to magnesium sulfate is 7.7 to 8.3:1, and the molar ratio of total water to magnesium sulfate is 19 to 21:
1. The total water includes added water and crystal water introduced by the magnesium sulfate raw material. The raw materials forming the inorganic gel matrix also include citric acid at 0.4% to 0.6% of the mass of light-burned magnesia powder and hydroxypropyl methylcellulose at 0.15% to 0.25% of the mass of light-burned magnesia powder.
6. The staggered through-type magnesium oxysulfide bonded plywood according to claim 5, characterized in that: The perforated core layer assembly has a non-perforated frame at the edge of the board surface. The width of the non-perforated frame is the shortest distance from the edge of the board surface to the edge of the nearest through hole, and is not less than 30 mm. The diameter Do of the first through hole is 12 mm, the diameter Dm of the second through hole is 8 mm, the center distance e is 4 mm, and the hole distance p is 60 mm.
7. A method for preparing a staggered, through-hole magnesium oxysulfide bonded plywood, used to prepare the staggered, through-hole magnesium oxysulfide bonded plywood according to any one of claims 1-6, characterized in that, Includes the following steps: S1. Provide 2n+1 layers of wood veneer, where n is 3, 4 or 5. Adjust the moisture content of the wood veneer to 9% to 11%, and determine the installation sequence from bottom to top according to the order in which the fiber directions of adjacent wood veneer layers cross. S2. Process corresponding and coaxial circular first through holes on the nth and n+2th wood veneer. Process circular second through holes on the n+1th wood veneer that correspond to the first through holes. Make the diameter of the second through hole smaller than the diameter of the first through hole, offset the second through hole relative to the corresponding first through hole, and make the projection overlap rate of the two 60% to 90%. Process the first through holes in a square array with a hole spacing of 55 to 70 mm, and make the second through holes in the same hole row offset in the same direction and the second through holes in adjacent hole rows offset in opposite directions. S3. Magnesium oxide-magnesium sulfate-water base slurry is prepared using lightly calcined magnesium oxide powder, magnesium sulfate and water; S4. Before the initial setting of the base slurry, the pore-filling slurry and the cementitious slurry are separated from the same mixing batch. The pore-filling slurry is prepared without the addition of closed-shell cenospheres. 25% to 35% of closed-shell cenospheres are added to the cementitious slurry based on its wet apparent volume, and the fresh mixing density of the cementitious slurry is 78% to 82% of the fresh mixing density of the pore-filling slurry. S5. Place the release bearing plate horizontally on the assembly platform, assemble the blanks from bottom to top according to the laying sequence, continuously apply the adhesive slurry to the area to be glued outside the through hole, and use a removable cover to avoid the through hole area. After laying and positioning the nth layer of wood veneer, fill its first through hole. Then, apply external adhesive grout to the hole, align and lay the (n+1)th layer of wood veneer and fill its second through hole. Then, apply external adhesive grout to the hole, align and lay the (n+2)th layer of wood veneer and fill its first through hole. This allows the filling grout that is filled later to contact and connect with the filling grout in the through hole below at the two bonding interfaces. Then, continue to lay the remaining complete wood veneers to form a board blank. S6. The slab is pre-pressed and warm-pressed sequentially to allow the filling slurry in the three corresponding through holes to solidify together to form a through-connector that penetrates the perforated core layer group, and the adhesive slurry is solidified to form a continuous sulfur-oxygen magnesium adhesive layer that is connected to the through-connector. S7. After pressing, perform staged depressurization; S8. Flatten, constrain, and cure the pressed plywood.
8. The method for preparing a staggered through-type magnesium oxysulfide bonded plywood according to claim 7, characterized in that: Based on the active magnesium oxide in the lightly calcined magnesium oxide powder, the molar ratio of active magnesium oxide to magnesium sulfate is 7.7-8.3:1, and the molar ratio of total water to magnesium sulfate is 19-21:
1. The base slurry also includes 0.4% to 0.6% citric acid and 0.15% to 0.25% hydroxypropyl methylcellulose, which are present in proportion to the mass of the light-burned magnesium oxide powder. The diameter Do of the first through hole is 10-14 mm, the diameter Dm of the second through hole is 7-10 mm, the Dm / Do ratio is 0.65-0.85, the center distance e between the second through hole and the corresponding first through hole is 3-5 mm, and the projection overlap rate of Do, Dm and e is 60%-90%.
9. The method for preparing a staggered through-type magnesium oxysulfide bonded plywood according to claim 8, characterized in that: The fresh density of the filling grout is 1.45–1.65 g / cm³, the fresh density of the adhesive grout is 1.15–1.30 g / cm³, and the wet application amount of the adhesive grout at each bonding interface is 150–180 g / (m²·adhesive layer). The mini slump spread of the grout was measured to be 45–60 mm using a cylinder with an inner diameter of 30 mm and a height of 30 mm. The water bleeding rate of the grout after standing for 30 minutes was no more than 1.0%. The theoretical wet filler mass m0 of a single borehole group is calculated as m0=ρf·π[Do²(tu+tl)+Dm²tm] / 4000, where ρf is the density of the freshly mixed slurry, and the units of Do, Dm, tu, tm and tl are mm respectively. The actual added mass deviates from m0 by no more than ±5%. After filling the borehole, the slurry is flush with or 0 to 0.20 mm higher than the borehole opening.
10. The method for preparing a staggered through-type magnesium oxysulfide bonded plywood according to claim 9, characterized in that: The initial setting time of the grout and the adhesive grout were measured separately, and the shorter of the two was used as the control initial setting time. The timing starts at the moment when the lightly calcined magnesium oxide powder begins to contact the magnesium sulfate solution. The time from t0 to the time when the slab is subjected to a pressure of 0.25 MPa as shown by the warm and high pressure pressing equipment shall not exceed 30 min and shall not exceed 50% of the controlled initial setting time. The time from the end of pre-pressing to the time when the warm and high pressure pressing equipment shows a pressure of 0.25 MPa shall not exceed 5 min. The slab is first pre-pressed at 0.25–0.35 MPa for 2–3 min, then warm-pressed at 50–60℃ and 1.0–1.3 MPa for 45–60 min. After pressing, the pressure is successively reduced to 0.6 MPa and held for 30 s, then reduced to 0.2 MPa and held for 30 s, and finally released to zero. After being removed from the slab, it is flattened and constrained under a surface pressure of 2–5 kPa for 4–8 h, and then cured in an environment of 23±2℃ and 60%±10% relative humidity for 14 days.